STUDIES ON STANDARD FORMATION ENTHALPIES OF RARE EARTH COMPOUNDS BY USING STRUCTURAL PARAMETERS - Yang F.; Feng L. (My University, 2000)
The atomic structural parameter P-i = (Z(i)*/n(i)*) (1 + n(i)*/n(i)) (1 + m(i)/Z) and the molecular structural parameter [GRAPHICS] are defined. The standard formation enthalpies (Delta(f)H(m)(phi)) of 74 species of rare earth compounds were studied with P, and the correlation coefficient is R > 0.94. The structural factors and the properties of rare earth compounds are influenced by the Z(i)*, n(i)*, n(i), m(i), Z. This study has special referential value to predict the properties of rare earth compounds.